If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12y + 9x = 15 Reorder the terms: 9x + 12y = 15 Solving 9x + 12y = 15 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-12y' to each side of the equation. 9x + 12y + -12y = 15 + -12y Combine like terms: 12y + -12y = 0 9x + 0 = 15 + -12y 9x = 15 + -12y Divide each side by '9'. x = 1.666666667 + -1.333333333y Simplifying x = 1.666666667 + -1.333333333y
| 4x^2+x-2x^2+3x= | | Solvek+4-5(k+2)=3k-2 | | X-8=9.11 | | 8t+(-8)=48 | | 3(-8+x+1)+8=80 | | 8t+(-7)=48 | | 24=5x+y | | -1(-3x+2)= | | 16(-18-17d)= | | 8t+(-7)=56 | | 6+3x+.5x^2=0 | | 2x^3-18x^2-36x= | | 6(x+3)-4=4x+28 | | 3x-22=2x+13 | | 20log(x)=26 | | 3x-3y-(2x-3y)= | | 4x+y=22500 | | 2G=2 | | 9y-7=14y+3 | | x-6*5=-40 | | r=2pir | | 2*z*y^2= | | 22s=16+(15s+12) | | C-100=3 | | 310-9x=13 | | c+4=4 | | 12+5n=n-7-1 | | 25x^2-30x-7=33 | | 6t+(-8)=48 | | 4S=84 | | f(x)=(x^2-4x-5)(x^2-8x+32) | | 2zy^2= |